Origins of native vascular plants of Antarctica: comments from a historical phytogeography viewpoint - Mosyakin, S.L.; Bezusko, L.G.; Mosyakin, A.S. (Цитология и генетика, 2007)
The article provides an overview of the problem of origin of the only native vascular plants of Antarctica, Deschampsia antartica (Poaceae) and Colobanthus quitensis (Caryophyllaceae), from the viewpoint of modern historical phytogeography and related fields of science.